Language and liberation : feminism, philosophy, and language - Hendricks, Christina; Oliver, Kelly, 1958- (Albany : State University of New York Press, 1999)
Presenting new scholarship in feminist language theory, this book addresses issues within diverse traditions, bringing together feminist positions, strategies, and styles in an original way. Gathering together authors with different backgrounds and methods, Language and Liberation puts this diverse scholarship into dialogue. The questions and concerns reflected in these essays are presented within the context of their historical background, provided by the editors' comprehensive introduction. These questions include: Is there a distinction between "female" and "male" language? What is the relationship of feminine/feminist identity to language? What is the value of metaphor for feminist theory and practice?
How to do (feminist) things with words / Christina Hendricks and Kelly Oliver -- Derogatory terms : racism, sexism, and the inferential role theory of meaning / Lynne Tirrell -- Discourse competence : or how to theorize strong women speakers / Sara Mills -- Surviving to speak new language : Mary Daly and Adrienne Rich / Jane Hedley -- From revolution to liberation : transforming hysterical discourse into analytic discourse / Georganna Ulary -- Disarticulated voices : feminism and philomela / Elissa Marder -- Confessional feminisms : rhetorical dimensions of first-person theorizing / Susan David Bernstein -- Postcolonial critic : shifting subjects, changing paradigms / Sangeeta Ray -- Sublime impersonation : the rhetoric of personification in Kant / Natalie Alexander -- Frege's metaphors / Andrea Nye -- Free gift or forced figure? Derrida's usage of hymen in "The Double Session" / Roberta Weston -- At the limits of discourse : heterogeneity, alterity, and the maternal body in Kristeva's thought / Ewa Płonowska Ziarek -- Writing (into) the symbolic : the maternal metaphor in Hélǹe Cixous / Lisa Walsh -- Language and the space of the feminine : Julia Kristeva and Luce Irigaray / Cynthia Baker.
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (viewed December 29th, 2024).
eBooks on EBSCOhost
Keywords: Language and languages -- Sex differences; Feminism; Feminism; Langage et langues -- Différences entre sexes; Féminisme.; feminism; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; Feminism; Language and languages -- Sex differences